Pengaruh Online Customer Review dan Online CUstomer Rating terhadap keputusan pembelian pada Marketplace shope - Risna Dwi Yuliani; Nur Hidayati; Aprilia Dian Evasari (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang, 2024)
Backgound. UNISKA is one of the universities with a significant number of Shopee users. Among these users, the majority come from the Faculty of Economics, particularly students from the Management program, which has a large student body at UNISKA. One of the notable findings from the researcher's observations of Management students is that many of them are Shopee users. In addition to shopping, they also engage in online selling through Shopee. Consequently, the marketplace features, such as online customer reviews and online customer ratings, attract significant attention from both academics and the general public. These features are considered key factors influencing consumer purchasing decisions on Shopee, as people often check store ratings before making a purchase. Additionally, the availability of numerous discounts and promotions further enhances consumer interest in transacting on the Shopee marketplace. Aim. This study aims to analyze the influence of Online Customer Review and Online Customer Rating on purchasing decisions in the Shopee marketplace Methods. This study uses a quantitative method using a sample of 94 respondents taken using the Non-probability Sampling technique, where the data was obtained through a questionnaire distributed to students of the Management Study Program at the Islamic University of Kadiri (UNISKA) class of 2020-2023 and analyzed using validity, reliability, classical assumptions, multiple linear regression, t-test, and f-test using SPSS 25 programs. Results. The results of the multiple linear regression analysis show that Online Customer Review (X1) with a regression coefficient value of 0.282 and Online Customer Rating (X2) with a regression coefficient value of 0.536 have a significant influence on Purchasing Decisions (Y) with a significance value of 0.000 each (p <0.05). The F test shows that both independent variables simultaneously influence purchasing decisions with a calculated F value of 56.540 and a significance of 0.000 (p <0.05). The conclusion of this study is that online customer reviews and online customer ratings play an important role in the purchasing decision-making process, especially among students. Based on these results, business actors in the marketplace are advised to pay more attention to and manage reviews and ratings given by customers in order to increase consumer trust and encourage increased sales.